IMPLEMENTASI PELAYANAN LEGALISASI DOKUMEN PUBLIK PADA KANTOR WILAYAH KEMENTERIAN HUKUM DAN HAM RIAU BERDASARKAN PERATURAN MENTERI HUKUM DAN HAM NOMOR 6 TAHUN 2022 TENTANG LAYANAN LEGALISASI APOSTILLE PADA DOKUMEN PUBLIK - Putri, Dini Cantika; Junaidi, Junaidi; Rauf, Muhammad A. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
One of the tasks of general legal administrative services in the legal divisionat the Riau Ministry of Law and Human Rights is to provide administrative servicesrelated to the legalization of documents that will be used domestically and abroad.Documents that will be used to travel inside or outside the country have a very longbureaucracy which then the Government of Indonesia through the Ministry of Lawand Human Rights has initiated to ratify the 1961 Apostille Convention, thusmaking Indonesia part of the Convention member state.The type of research used is sociological juridical, namely researchconducted by identifying the law and how the effectiveness of the implementation ofthe law applies in society. Because in this study the authors directly conductedresearch at the location or place under study to provide a complete and cleardescription of the problem under study.The conclusions that can be obtained from the research results are First,the implementation of Public Document Legalization services at the Riau RegionalOffice of the Ministry of Law and Human Rights has challenges related to fieldproblems, limited resources, process complexity, time, conflicts with Article 8 ofPermenkumham No. 6 of 2022 and the need for proper enforcement of rules andlegal suitability. Simplified and more accessible services reflect efforts to adhere tothe principles of legality and efficiency. Second, Supporting and inhibiting factorsin the Public Document Legalization service system at the Riau Regional Office ofthe Ministry of Law and Human Rights basically have a number of supportingfactors that strengthen the public document legalization service system such asAdoption of Technology and Online Systems. Third, the efforts of the Ministry ofLaw and Human Rights Riau in overcoming problems regarding the service ofLegalization of Public Documents (Apostille) by involving steps that includedigitization of services, increased access to information, infrastructure investment,collaboration with related parties, and improvement of processes and services.Keywords: Implementation, Service, Document Legalization, Public Service.